Aplicação em fábrica de ensaios não destrutivos em lajes alveolares protendidas para a verificação da conformidade de projeto - Bazilio, Luis Fernando Borzi (2021)
To obtain the strength supported by hollow core slabs it is necessary to perform standardized destructive tests, and in these tests it is possible to verify the product's compliance with the design. ABNT NBR 14861 (2011) does not allow the performance of simplified tests in a manufacturing environment due to lack of studies in the area, while ABNT NBR 9062 (2017) allows experimental verifications as part of the design procedure. Based on the above, the purpose of this paper is to verify the compliance of hollow core slabs with the design, by performing non-destructive tests in a factory environment in order to avoid destructive testing and to reduce waste of material, time and cost in the production of prestressed hollow core slabs.